EFFICACY OF PROPHYLACTIC ANTIBIOTICS IN REDUCING POST-TONSILLECTOMY HAEMORRHAGE - Sheikh, Nadeem Ahmed; Nadeem, Kanwal (Journal of Ayub Medical College Abbottabad, 2020)
Background: This study aims toward establishing the impact of prophylactic pre-operative antimicrobial therapy on tonsillectomy related haemorrhage. Methods: In this randomized controlled trial conducted at Combined Military Hospital, Abbottabad from January 2017 till August 2019, 121 children and adult patients who had consented and had undergone tonsillectomy were evaluated for procedure related haemorrhage. Results: Incidence rate of secondary post-tonsillectomy haemorrhage and need for re-hospitalization was significantly less in patients who had completed pre-operative prophylactic antibiotics. Patient-reported secondary haemorrhage was recorded in 4.59% (n=9) cases who did not receive pre-operative antibiotic prophylaxis, thereby increasing morbidity and prolonging hospital stay. Secondary post-operative bleeding only occurred in 1.18% (n=2) patients who received appropriate pre-operative anti-microbial prophylaxis. Conclusion: We strongly imply that prophylactic pre-operative antibiotics reduce procedure related complications in all patients undergoing tonsillectomy. Keywords: Tonsillectomy, morbidity, haemorrhage, anti-bacterial agents